2007
DOI: 10.1111/j.1365-2443.2007.01101.x
|View full text |Cite
|
Sign up to set email alerts
|

PX‐RICS, a novel splicing variant of RICS, is a main isoform expressed during neural development

Abstract: In our previous study, we identified RICS, a novel β β β β -catenin-interacting protein with the GAP activity toward Cdc42 and Rac1, and found that RICS plays an important role in the regulation of neural functions, including postsynaptic NMDA signaling and neurite outgrowth. Here we report the characterization of an N-terminal splicing variant of RICS, termed PX-RICS, which has additional phox homology (PX) and src homology 3 (SH3) domains in its N-terminal region. The PX domain of PX-RICS interacted specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
32
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 23 publications
0
32
0
2
Order By: Relevance
“…Antibodies-Rabbit polyclonal antibody to PX-RICS was generated as described previously (15). The commercially available antibodies used in this study were as follows.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Antibodies-Rabbit polyclonal antibody to PX-RICS was generated as described previously (15). The commercially available antibodies used in this study were as follows.…”
Section: Methodsmentioning
confidence: 99%
“…RICS is expressed predominantly in neurons of the brain and localized to the growth cone and postsynaptic density, where it regulates neurite extension and presumably N-methyl-D-aspartate signaling (14). In contrast, PX-RICS is expressed in a wide variety of tissues and cell lines and localized to the ER and cis-Golgi (13,15). Our recent study has revealed that PX-RICS facilitates ER-to-Golgi transport of the N-cadherin-␤-catenin complex through its direct interaction with ␤-catenin, Cdc42, ␥-aminobutyric acid type A receptor-associated protein (GABARAP) and phosphatidylinositol 4-phosphate (PI4P) (13).…”
mentioning
confidence: 99%
See 3 more Smart Citations